PEMAHAMAN MITIGASI KEBAKARAN RUMAH TANGGA DI WILAYAH KELURAHAN PURWODININGRATAN SURAKARTA - eska, Eska Dwi Prajayanti (Asawika : Media Sosialisasi Abdimas Widya Karya, 2025)
Background:Fires can occur at any time unexpectedly and unintentionally, potentially destroying houses, crops, and other property, leading to significant losses of possessions and even human lives. Negligence is the most common cause of household fires, often stemming from electrical short circuits or gas leaks. In addition, the high incidence of fires in the Purwodiningratan sub-district is due to densely packed housing, unregulated use of land for home-based industries, and poor sanitation in the area.Method: The community service program was carried out in two educational stages. The first stage involved a lecture on household fire mitigation, and the second stage consisted of a demonstration on how to extinguish household fires, such as gas explosions and the use of fire extinguishers (APAR).Results: There was an increase in knowledge before and after the household fire mitigation education was provided.Conclusion: There is an effect of fire disaster mitigation education using lecture and demonstration methods on the knowledge level of residents in RT 06, Purwodiningratan Sub-District, Surakarta.